Review of calls to NHS Direct related to attendance in the paediatric emergency department. Issue 12 (27th November 2006) - Stewart, B; Fairhurst, R; Markland, J; Marzouk, O
Abstract : Objective: To examine the outcomes of calls to NHS Direct (NHS-D) in relation to attendance at the accident and emergency (A&E) department. Design: A prospective collection of data about consecutive calls to NHS-D North West Coast was matched with attendances at the A&E department over a period of 3 months. Setting: NHS-D Regional Trust and a large urban paediatric A&E department. Patients: Children and young adults aged <16 years living in local postal code areas. Main outcome measures: To examine (1) whether advice given by NHS-D was followed and (2) the differences in disease severity and necessity of attendance of patients referred by NHS-D and those referred by general practitioners and self-presenters. Results: The relationship between the advice given and subsequent action is complex. Only 70% of calls advised to attend the A&E department did so. A further 1% (176) were advised not to attend the A&E department did in fact attend the department. Patients referred by NHS-D represented only 3.2% of department attendances. There was little difference in the triage categories of the presenting groups, but there were significantly less admissions (p<0.01) in the NHS-D group. Conclusions: Delivering telephone advice about illness severity in children is difficult as visual clues are so important. More collaborative prospective studies are needed, including with primary care, to understand families' choices, and to refine and assess NHS-D's ability to discriminate those requiring further clinical assessment.